Creating universal health care in Ireland: A legal context. Issue 6 (June 2021) - Lau, Manfred; Larkin, Charles; Harty, Michael; Corbet, Shaen
Highlights: We establish a working definition of a constitutional right-to-health protection in Ireland We propose that a legal framework exists based on South African parallels This right strengthens health policy goals such as universal health care National rights to health have observable correlations with improved public health In Ireland, a right-to-health would complement existing right to primary education Abstract: In this paper we establish a working definition of, and develop a legal rationale for, the insertion of a constitutional Right to Health (RTH) protection in the Constitution of Ireland. We propose that a legal framework exists for the judicial enforcement of a right to health in Ireland, as based on parallels drawn between Irish case law and that of RSA, a comparable common law constitutional democracy with a developed jurisprudential approach to its constitutional RTH. When modelled after precedential international provisions, this right strengthens and defends health policy goals (such as universal health care) through a common-law system of governmental accountability. Additionally, national rights to health have observable correlations with improved public health, and it stimulates institutional initiatives. The 1937 Constitution of Ireland includes several personal, social, and economic rights, and a RTH would complement the existing right to primary education as a socio-economic right. We note these considerations were discussed during the legislative proposal made in the 32 nd Dáil for a constitutional RTH, which emerged in response to Ireland's ongoing efforts toward health policy reform.